Short-acting beta-2 agonist prescription patterns and clinical outcomes in Chinese patients with asthma: an observational study in mainland China for the SABINA programme. (August 2022) - Bao, Wuping; Zhang, Yingying; Hang, Jingqing; Guo, Yubiao; Tang, Wei; Yun, Chunmei; Deng, Jingmin; Jin, Meiling; Lai, Kefang; Yu, Huapeng; Beekman, Maarten; Zhou, Xin; et al.
Objectives: The SABINA CHINA study aimed to determine prescription data for asthma medication with a focus on SABA and ICS in a representative population of patients with asthma in China. Methods: SABINA China was a multicentre, observational, cross-sectional study with data collected retrospectively from a convenience sample of 25 tertiary centres across China. Patients (age ⩾ 12 years) with ⩾3 consultations/year were enrolled. Data were collected on clinical characteristics, asthma severity, and symptom control (as per GINA 2017), treatment and history of severe exacerbations over the past year. SABA over-prescription was defined as ⩾3 SABA canisters/year. Descriptive statistics are presented. Results: Between March and August 2020, 498 patients were included in the outcome analysis. Mean (SD) age was 48.7 (15.0) years, 57.9% were female and 91% had moderate-to-severe asthma ( n  = 453). Overall, 12.5% ( n  = 62) and 26.4% ( n  = 131) of patients had uncontrolled and partly controlled asthma, respectively. SABA add-on was prescribed to 20.3% ( n  = 101) of patients; one patient with moderate-to-severe asthma was prescribed SABA-alone. SABA over-prescription in the overall population was 4.0% ( n  = 20; all with moderate-to-severe asthma) and 19.8% (20/101) among those prescribed SABA add-on. In the mild asthma group, 50% ( n  = 22) were prescribed ICS/LABA and 43.2% ( n  = 19) were prescribed LTRA. Among those with moderate-to-severe asthma, 97.4% ( n  = 441) were prescribed ICS/LABA and 55.0% ( n  = 249) were prescribed LTRA. Approximately 30% of patients ( n  = 149) experienced ⩾1% and 6.6% ( n  = 33) ⩾3 severe exacerbations in the preceding year; mean annual number of severe exacerbation/patient was 0.6 (1.2). Among those prescribed SABA add-on, ICS/LABA and LTRA (non-mutually exclusive groups due to overlapping prescriptions), 54.5%, 29.9%, and 35.3% had ⩾1 severe exacerbations, respectively. Conclusion: Among patients with predominantly moderate-to-severe asthma managed in tertiary care and were prescribed SABA, 1 in 5 received ⩾3 canisters/year. Fewer patients who received ICS/LABA prescriptions experienced annual exacerbations than those prescribed SABA add-on.